Du féminin dans les discours militaires au XVIIIe siècle - Naoko Seriu (Genre & Histoire)
The invention of a new figure of the soldier was at stake in the military reforms of the second half of the eighteenth century. In response to the reform efforts of the ministers of war, officers wrote memoranda about what a soldier should be. At the margins of these proposals, one finds comments that denounce women as enemies of discipline. The feminine figure also appears in the denunciation of unworthy soldiers who should then be dressed as female. Echoing the debate on luxury, officers produced discourses that degrade women and situate them outside the pale of humanity. To what extent is this denunication within military discourse present in actual practice? Through the analysis of accounts and stories about military life, from both officiers and soldiers, this article demonstrates how this categorization functioned, and how the mere mentioning of woman ensured the cohesion of this male society.